(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Premessa - 2. Il libro IV come introduzione al tema - 3. I magna latrocinia - 4. Lo svolgimento logico della tesi agostiniana sul rapporto tra Stato e giustizia - 5. Cristo come unico criterio per la giustizia/virtù/felicità - 6. Il libro XIX come allargamento dei confini della legittimità dello Stato - 7. Le due civitates - 8. L’assetto delle due città nel saeculum - 9. L’identificazione della CD con la Chiesa - 10. La predestinazione quale criterio di ascrizione alle due civitates - 11. Il DcD come strumento politico - 12. Una conseguenza imprevedibile (?): la secolarizzazione - 13. Conclusione. Augustine’s De civitate Dei and its influence on the process of secularization of the State ABSTRACT: Is justice essential to State? Augustine, in the fourth book of the City of God, starts with a strict idea of State, but then widens the definition: he grants that also an unjust - not based on the real God - State may be a real State. This option seems to be prominent in the process of secularization enacted in the last centuries, but it’s also connected to other matter: the predestination, the identification (or not) between the City of God and the Church, and so on. Methodologically, I tried to read what Augustine really wrote and not what others said about his works.